Effects of intermedin on dorsal root ganglia in the transmission of neuropathic pain in chronic constriction injury rats. (July 2015) - Xiong, Wei; Qiu, Shu‐yi; Xu, Ling‐yun; Zhang, Chun‐ping; Yi, Yun; Wu, Qin; Huang, Li‐ping; Liu, Shuang‐mei; Wu, Bing; Peng, Li‐chao; Song, Miao‐miao; Gao, Yun; et al.
Summary Neuropathic pain is a common and severely disabling state that affects millions of people worldwide. The P2X3 receptor plays a crucial role in facilitating pain transmission. Intermedin (IMD), which is also known as adrenomedullin 2 (AMD2) is a newly discovered hormone that is a member of the calcitonin/calcitonin gene‐related peptide family. The present research investigates the effects of IMD on pain transmission in neuropathic pain states as mediated by P2X3 receptors in dorsal root ganglia (DRG). Chronic constriction injury (CCI) rats were used as the neuropathic pain model. Adult male Sprague‐Dawley rats were randomly assigned to five groups as follows: blank control group (Control), sham operation group (Sham), CCI rats treated with saline group (CCI+NS), CCI rats treated with IMD1–53 group (CCI+IMD1–53), and CCI rats treated with IMD inhibitor IMD14–47 group (CCI+IMD14–47). The mechanical withdrawal threshold (MWT) was tested by the von Frey method, and the thermal withdrawal latency (TWL) was tested via automatic thermal stimulus instruments. Changes in the expression of P2X3 receptors and IMD in CCI rat L4/L5 DRG were detected using immunohistochemistry, reverse transcription‐polymerase chain reaction, and Western blotting. After treatment with intrathecal injection (i.t.), mechanical and thermal hyperalgesia in the CCI+IMD1–53 group was maintained, but MWT and TWL in the CCI+IMD14–47 groups increased. The expression levels of P2X3 receptors and IMD in L4/L5 DRG in the CCI+NS and CCI+IMD1–53 groups were significantly increased compared with those in the Control group or the Sham group. After application of IMD14–47 in CCI rats, there was a decrease in the expression levels of P2X3 receptors and IMD in L4/L5 DRG. The phosphorylation of p38 and ERK1/2 in L4/L5 DRG in the CCI+NS group and the CCI+IMD1–53 group was stronger than that in the Control group or the Sham group; however, the phosphorylation of p38 and ERK1/2 in the CCI+IMD14–47 group was much lower than that in the CCI+NS group or the CCI+IMD1–53 group. Our findings indicate that IMD might increase the sensitization effects of IMD on P2X3 receptors to alleviate chronic neuropathic pain injury. The IMD agonist IMD1–53 might enhance nociceptive responses mediated by P2X3 receptors in neuropathic pain, and the IMD inhibitor IMD14–47 could inhibit the sensitization of the P2X3 receptor in chronic neuropathic pain injury.